Performance evaluation of Garlic (Allium sativum L.) in the plains of Kerala - S. Jalaja Menon (Journal of Horticultural Sciences, 2018)
Kerala, the spice bowl of India is popular for tropical spice crops like pepper, cardamom, nutmeg etc. Garlic, an important foreign exchange earner of India is produced mostly in the states like Madhya Pradesh, Rajasthan and Gujarat. In Kerala it is grown commercially in two unique rain shadow pockets, Kanthalloor and Vattavada regions of Devikulam block of Idukki district. Although garlic is grown in the high ranges of Kerala, its cultivation in plains are not evaluated so far. Generally cool season crops performs well inplains when grown during October – March. Hence the present study was conducted to evaluate the performance of two genotypes Singapore and Mettupalayam in the plains. The two garlic genotypes were grown as pot culture during October – February in the year 2016-2017, in the plains of Thrissur district, the central part of Kerala. Among the two types Mettupalayam was found to be recorded higher Bulb weight (14.53g) and number of cloves per bulb (4.2), but it was less compared to that grown in high ranges (17.19g and 11.9 respectively). Hence the study revealed the possibilities of garlic cultivation in the plains of Thrissur district of Kerala with some refinements in agro techniques.